Correlation between multiple ionization and fragmentation of small hydrocarbon molecules induced by fast heavy ions. (July 2015) - Majima, T; Yoshida, S O; Asai, T; Matsubara, M; Tsuchida, H; Itoh, A
Synopsis: We investigate correlations between multiple ionization and fragmentation processes of the acetylene, ethylene and ethane molecules in collisions with 0.58-1.2 MeV C +, 2+ ions under specific charge changing conditions. The number of ionized electrons are observed directly by an electron counting technique. Fragmentation processes are discussed in terms of the charge state of parent ions prior to fragmentation. The correlation results reveal evidently roles of the charge state and the internal excitation in the molecular fragmentation processes.